2022
DOI: 10.3171/2021.4.spine2140
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoradiological characteristics of primary spinal cord H3 K27M-mutant diffuse midline glioma

Abstract: OBJECTIVE Primary spinal cord H3 K27M-mutant diffuse midline glioma (DMG) is a rare and devastating pathological entity. However, little attention has been paid to this disease. As a result, its clinicoradiological characteristics have yet to be described. The aim of this study was to describe the clinicoradiological characteristics of primary intramedullary H3 K27M-mutant DMG and to compare this tumor with the H3 K27 wild-type to explore potential features that could differentiate the two. METHODS A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 40 publications
2
20
1
1
Order By: Relevance
“…However, several reports the incidence of H3 K27-altered increases along with histological grade. [24,25] The same trend was observed in in our study, although no statistical signi cance was observed. Due to the size of the cohort, we could not perform multivariate analysis to determine whether there is collinearity between these two prognostic factors.…”
Section: Discussionsupporting
confidence: 89%
“…However, several reports the incidence of H3 K27-altered increases along with histological grade. [24,25] The same trend was observed in in our study, although no statistical signi cance was observed. Due to the size of the cohort, we could not perform multivariate analysis to determine whether there is collinearity between these two prognostic factors.…”
Section: Discussionsupporting
confidence: 89%
“…Somatic missense mutations at amino acid position 27 of the H3F3A or HIST1H3B genes are commonly seen in astrocytomas of midline structures, including the pons, thalamus, and spinal cord, resulting in the discrete entity designated diffuse midline glioma, H3 K27M-altered ( 87 ). They are estimated to account approximately between 18% and 55% of intramedullary astrocytomas ( 86 , 88 , 89 ). Originally designed in the 2016 WHO guidelines as H3 K27M-mutant lesions, the updated nomenclature reflects other mechanisms can alter the pathway beyond genetic mutations ( 7 ).…”
Section: Molecular Landscapementioning
confidence: 99%
“…Although they can appear in several midline structures, the spinal cord is the most common site of H3 K27M-altered gliomas in adults ( 93 ). They are designated WHO Grade 4, although their underlying microscopic appearance may appear Grade 2, 3, or 4 ( 88 , 94 ). Indeed, the majority of H3 K27M-altered gliomas appear as high-grade lesions, but approximately 40% can appear as Grade 2 in histology ( 88 , 95 ).…”
Section: Molecular Landscapementioning
confidence: 99%
See 2 more Smart Citations